Corrigendum: Factors causing rework and their impact on projects’ performance in Egypt - Al-Janabi, Assim Muwafaq; Abdel-Monem, Mohamed Shawky; El-Dash, Karim Mohamed (Journal of Civil Engineering and Management, 2021)
The article “Factors causing rework and their impact on projects’ performance in Egypt” by Assim Muwafaq Al-Janabi, Mohamed Shawky Abdel-Monem, Karim Mohamed El-Dash, published in the research journal Journal of Civil Engineering and Management, 26(7), 666-689, https://doi.org/10.3846/jcem.2020.12916 contained following errors:1. Some confusion related to ($) value against (EGP) appeared at Research method paragraph, page 670. Instead of ($1 = 1.65 EGP) the value should read:($ 1 ≅ 16.5 EGP)2. A mistake in establishing the correct contract value for the automatic multistorey car parking project appeared at Research method paragraph page 670, Table 2. The value 2.49 billion should read:249 million.Corrected version of the article is available online.The authors regret the errors.